Frankincense and myrrh essential oils and burn incense fume against micro-inhabitants of sacral ambients. Wisdom of the ancients? - Grbic, M. L.; Unkovic, N.; Dimkic, I.; Janackovic, P.; Gavrilovic, M.; Stanojevic, O.; Vukojevic, J.
Essential oils obtained from resins of Boswellia carteri Birdw. and Commiphora myrrha (Nees)Engl., commonly known as frankincense and true myrrh respectively, have been used extensively since 2800 BCE for the treatment of skin sores, wounds, teeth, inflammation, and urinary tract diseases in traditional medicine; for preparation of mummification balms and unguents; and also as incense and perfumes. Since ancient times, burning of frankincense and myrrh in places of worship for spiritual purposes and contemplation (a ubiquitous practice across various religions)had hygienic functions, to refine the smell and reduce contagion by purifying the indoor air.
Keywords: BACTERIA; BOSWELLIA CARTERI; CHURCHES; COMMIPHORA MYRRHA; FUNGI; RESINS